Exoticization of Indigenous Bali Wisdom: Impacts on Cultural and Tourism Sustainability - I Ketut Surata (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
Indigenous Balinese wisdom, embodied in rituals, performing arts, and communal traditions, has long been central to cultural identity and destination distinctiveness. Yet, the acceleration of global tourism has intensified the exoticization of indigenous wisdom, whereby sacred practices are reconfigured into staged attractions that privilege spectacle over meaning. While such transformations provide immediate economic gains, they simultaneously weaken cultural authenticity, disrupt inter-generational knowledge transmission, and generate tensions within host communities. This study critically examines the exoticization of Indigenous Balinese wisdom within contemporary tourism and its implications for cultural and tourism sustainability. Unlike prior studies that treat commodification as a descriptive phenomenon, this research introduces a multidimensional analytical framework that integrates cultural commodification, staged authenticity, and sustainability governance into a unified model. It further advances existing scholarship by operationalizing exoticization through measurable multidimensional indicators, including cultural distortion, inter-generational knowledge disruption, governance misalignment, and community agency and proposing participatory, indicator-based approaches to assess and govern the impacts of tourism on indigenous cultural integrity. Findings underscore that safeguarding Balinese cultural sustainability requires inclusive strategies that empower local actors, balance stakeholder interests, and embed cultural integrity into tourism planning. The study offers both theoretical insights and practical guidelines, providing a replaceable model for heritage destinations confronting similar pressures worldwide.